Efeitos do exercício físico sobre a expressão da proteína glial fibrilar ácida (GFAP) e comportamento motor de ratos submetidos ao modelo de doença de Parkinson induzida por 6-OHDA - Dutra, Márcio Ferreira (2009)
The aim of this study was to investigate whether exercise could improve motor behavioral deficits and alter expression of glial fibrillary acidic protein (GFAP) in dorsal striatum in a 6-hydroxydopamine (6-OHDA) rat model of Parkinson’s disease (PD). To this end, animals were randomly divided into 4 groups: sham sedentary (SS, n = 7); sham trained (ST, n=8); lesioned sedentary (LS, n=8) and lesioned trained (LT, n = 8). Rats were unilaterally lesioned with 6-OHDA (10 μg/3 μg) injected into the left medial forebrain bundle and sham groups were only injected with vehicle solution. The treadmill training protocol consisted of running with progressive increase in velocity, 5 days/week, during 4 weeks. Behavioral tasks were applied to asses the motor abilities of all animals prior to 6-OHDA injection and at 8th and 29th days post-injection. The tyrosine hydroxylase (TH - in substantia nigra pars compacta) and GFAP (in dorsal striatum) immunostaining was evaluated by semiquantitative analysis of the intensity (optical density - OD). The 6-OHDA lesion decreased the OD of TH and increased the OD of GFAP. In addition, the 6-OHDA lesion increased the number of ipsilateral rotations induced by methylphenidate (40 mg/kg, i.p., 30 min) and caused motor behavioral deficits. On the other hand, the treadmill training resulted in an increase in maximal exercise capacity in both trained groups (ST and LT). The training was able to reduce the number of ipsilateral rotations and ameliorated the motor behavioral deficits on 8th and 29th days postlesion. Interestingly, the exercise led to a significant increase in OD of GFAP in the LT group while there was no such effect in ST group. Our results indicate that treadmill training can improve motor behavioral deficits and suggest that the effects of exercise may be directly or, indirectly, mediated by astrocytes, as an increase in GFAP was observed in the dorsal striatum. Nevertheless, these are the first data showing an increase in GFAP expression post-exercise in this model and further research is needed to determine the precise action of exercise on astrocytes in Parkinson’s disease.